Pendekatan Emosional Masyarakat Desa Negara Batin II Untuk Meningkatkan Kesadaran Pentingnya Pendidikan Bagi Anak - Hermin Syamsiah; Meryna Putri Utami (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
The community's understanding, especially parents, of the awareness of the importance of education needs to be increased through an emotional approach. This was done in order to be able to provide a good education, including education in schools, families, and in the community, as well as encouraging the community to consider encouraging children to get education to a higher level, to prepare children as the next generation of the nation. The community environment is very influential in improving children's education, as well as the family environment. This research aims to make people aware of the importance of education for children. The method used in this research activity is to use descriptive research methods, which focus on problems that are appropriate to what they were at the time the research took place. In this study, the presentation of data using observation techniques, interviews and documentation. Based on the results of the study, there were 115 children who had dropped out of school. Using a random sampling technique, the researchers used the sample by drawing lots and obtained a sample of 30 children who had dropped out of school. The level of education of parents and the low economic income of the family is one of the factors causing children to drop out of school. With the directives using an emotional approach that the researchers carried out to the Negara Batin II village community, it turned out that it greatly influenced the community's better and increased views of the importance of education for children.